Intellectuals and the State in Iran - Alireza Asgharzadeh (International Institute of Islamic Thought, 2004)
Negin Nabavi’s Intellectuals and the State in Iran comes at a time when a process of soul-searching by some Iranian intellectuals that started immediately after the triumph of Islamic revolution has now faded away, without yielding any satisfactory results. This process was inspired by the question: What role did the (secular left-leaning) intellectuals play in the revolution’s triumph, which culminated in an Islamic state inherently opposed to the activities of these same intellectuals? This important topic, of course, gives rise to the familiar question of “What is meant by an intellectual?” which Nabavi addresses in the book’s first part. Having given a historical perspective on the development and evolution of intellectualism in Iran, she concludes that a distinguishing character of the Iranian intellectual was “the intellectual’s task to take a stance and engage with issues in society” (p. 3); where “dissent” was “a necessary component in the career of any Iranian intellectual” (p. 18). In part two, Nabavi discusses the processes that led to the “radicalization of the Iranian intellectual.” Here she explores the emergence of what she calls “the Third-Worldist intellectual” and the cooptation of a great number of intellectuals by the Pahlavi regime . According to her, during this period (1963-70) “the notions of the ‘native’ and the ‘authentic’ became so pervasive that even the establishment could not remain impervious to them” (p. 106). The epilogue briefly touches upon the relationships between intellectuals and the revolution, where the author concludes that the intellectuals “lost out in the year that followed the revolution” (p. 149) ...